139k views
1 vote
Given that ƒ(x) = x2 + 1 and g(x) = –3, multiply the functions (g · ƒ)(x).

// not A

Given that ƒ(x) = x2 + 1 and g(x) = –3, multiply the functions (g · ƒ)(x). // not-example-1
User Adrianmcli
by
4.9k points

1 Answer

6 votes

Answer:

Option B

(g × ƒ)(x) = 3x² + 3

Explanation:

Given;

  • ƒ(x) = x² + 1
  • g(x) = – 3

To Find;

  • (g × ƒ)(x)

Now,

(g × ƒ)(x)

(x² + 1)(– 3)

-3x² – 3 = 0 (Assuming zero, so we can take minus as common)

3x² + 3

Thus, The answer is 3x² + 3.

-TheUnknownScientist 72

User Guillermo Espert
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.